Does bendamustine impact the mobilization of peripheral blood stem cells? A multicenter retrospective study of 23 cases. Issue 5 (3rd May 2016) - Gac, Anne-Claire; Azar, Nabih; Daguindau, Etienne; Cartron, Guillaume; Fornecker, Luc M.; Gyan, Emmanuel; Broussais-Guillaumot, Florence; Garidi, Reda; Choufi, Bachra; Chantepie, Sylvain P.; Béné, Marie-Christine; Guiéze, Romain; et al.
Abstract: Bendamustine is used in the treatment of different relapsing or refractory subtypes of lymphoma. Its impact on the yield of peripheral blood stem cells is not well known. Twenty three patients who received bendamustine followed immediately or after another chemotherapy by stem cell mobilization (SCM) were included. The patients were divided into two groups: group 1 ( n =17), in whom SCM was performed immediately after bendamustine chemotherapy, and group 2 ( n =6), in whom SCM was performed after another cycle of chemotherapy. The success rate of mobilization after Bendamustine+/−plerixafor was 36% (eight cytapheresis succeeded for a total number of 22 cytapheresis); and 75% after other approaches (chemotherapy based or steady state) used for patients who received bendamustine previously. Although bendamustine used alone was not an effective drug to mobilize stem cells, this agent does not seem to have detrimental effects on subsequent SCM.